2017
DOI: 10.1088/2053-1583/aa7a32
|View full text |Cite
|
Sign up to set email alerts
|

The structural phases and vibrational properties of Mo 1−x W x Te 2 alloys

Abstract: The structural polymorphism in transition metal dichalcogenides (TMDs) provides exciting opportunities for developing advanced electronics. For example, MoTe 2 crystallizes in the 2H semiconducting phase at ambient temperature and pressure, but transitions into the 1T′ semimetallic phase at high temperatures. Alloying MoTe 2 with WTe 2 reduces the energy barrier between these two phases, while also allowing access to the T d Weyl semimetal phase. The −RECEIVED

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 51 publications
6
48
0
Order By: Relevance
“…MoTe2 is one of the few TMDCs in that it stabilizes both semiconducting and metallic polytypes, transitions between which can be further controlled by temperature, alloying, strain, and electrostatic gating [4][5][6][7][8][9][10]. 1T-MoTe2 is unstable, however-distortion of in-plane bonds gives rise to an enlarged monoclinic unit cell ( or 1T' phase) at room temperature [11].…”
mentioning
confidence: 99%
“…MoTe2 is one of the few TMDCs in that it stabilizes both semiconducting and metallic polytypes, transitions between which can be further controlled by temperature, alloying, strain, and electrostatic gating [4][5][6][7][8][9][10]. 1T-MoTe2 is unstable, however-distortion of in-plane bonds gives rise to an enlarged monoclinic unit cell ( or 1T' phase) at room temperature [11].…”
mentioning
confidence: 99%
“…As previously discussed, investigations into the kinetics of phase transitions in monolayer MoTe 2 and other monolayer materials are nascent and much remains unknown. Experimental studies of thermal phase transitions in MoTe 2 have been reported to occur on timescales of several hours at high temperatures, 12,14 while other reports suggest that the kinetics can occur on timescales of minutes or less at ambient temperatures and below. 16,18 The large variability in these reports suggests that there is potential to engineer the kinetics of these phase transitions to achieve desired electronic or other device timescales.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 The fast and reversible phase transition in Ge 2 Sb 2 Te 5 alloys can be achieved by Joule heating, 5 and this process can be employed in nonvolatile phase-change memory with lower programming voltages and higher memory densities than mainstream nonvolatile memory technologies. 2,3,6,7 Some layered and two-dimensional (2D) materials including MoTe 2 have been reported or predicted to exhibit structural phase changes during chemical processes, 8,9 temperature changes, [10][11][12][13][14] and tensile strains. 15,16 Some single layer transition metal dichalcogenide (TMD) monolayers, including monolayer MoTe 2 , can exist in a semiconducting trigonal prismatic state found in the bulk 2H structure, a semimetallic distorted octahedral state found in the bulk 1T′ monoclinic and orthorhombic (sometimes referred to as T d ) phases, and possibly other structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mo x W 1‐x Te 2 , the most attractive group‐6 TMD‐based Type‐II TWS by theoretical prediction, contains tunable topological surface states and is more stable than other TWS of the binary compounds, such as WTe 2 and MoTe 2 . The strength of the topological surface states of Mo x W 1‐x Te 2 depends directly on the length of Fermi arc, which can be tuned at the Brillouin zone by doping Mo (from 2 to 40%) into the WTe 2 system . Mo x W 1‐x Te 2 is a layered crystal, in which a single layer of W/Mo is sandwiched between two Te layers and stacked along the z‐axis via van der Waals interactions (Figure a).…”
Section: Introductionmentioning
confidence: 99%